Risk factors and incidence of contrast-induced acute kidney injury associated with diagnostic or interventional coronary angiography - Maskey, Abhishek; Kafle, Ram Chandra; Lamsal, Sudip (Journal of Advances in Internal Medicine, 2020)
Background and Aims: Coronary angiography/ interventions depend on iodinated contrast media (CM) and consequently pose risk of contrast-induced acute kidney injury (CI-AKI). This is an important complication that accounts for a significant number of cases of hospital-acquired kidney injury, with adverse effects on prognosis and health care. This study aimed to assess incidence and evaluate risk factor CI-AKI associated with diagnostic or interventional coronary angiography. Methods: A prospective cross sectional observational hospital based study was conducted. All patients undergoing percutaneous coronary angiography in Manipal Teaching Hospital from May 1, 2019 to April 31, 2020 were included in this study. Appropriate statistical tests were used to analyse results and P <0.05 was considered statistically significant. Results: We evaluated a total of 155 patients. Among them, 90 (58%) were male and 65 (42%) female. The mean age of patients was 62.74 ± 13.9 years. Overall incidence of contrast induced acute kidney injury was 15.48%. CI-AKI was observed to be more common in patient with advance age and diabetes. Apart from advance age and diabetes, none of the other conventional risk factors such as hypertension, anaemia, volume of contrast, baseline chronic kidney disease found to have a significant association with incidence of CI-AKI. None of the patients in our study required renal replacement therapy, and there was no mortality. Conclusion: The overall incidence of CI-AKI after coronary intervention in this study is high. Patients with advance age and diabetes were at high risk of CI-AKI.